Mastering Canon EOS Flash Photography, 2nd Edition, 2nd Edition - Guy, NK (Rocky Nook, 2016)
In this updated, second edition of the authoritative, bestselling Mastering Canon EOS Flash Photography, photographer NK Guy brings the book fully up to date, with coverage of all the newest Canon gear that has hit the market since the first edition published in 2010. This includes coverage of the radio-enabled Canon Speedlite 600EX-RT and Canon Speedlite Transmitter ST-E3-RT, as well as the other Speedlites that have released since the first edition's publication: Canon Speedlite 90EX, 270EX II, 320EX, and 600EX. Digital cameras and flash technology have truly revolutionized photography in the 21st century. Originally seen simply as a practical way to illuminate dark scenes with portable light, flash today is used for a host of creative and nuanced applications, including supplementing daylight, designing complex scenes lit by multiple light sources, and simply creating beautiful, controllable light for portraiture. With LCD screens on DSLRs, the ability to get instant feedback on lighting setups is a great help in advancing one's lighting capabilities and encouraging experimentation. However, flash photography can still be a difficult artistic and technical challenge. It's simple to get that harsh deer-in-the-headlights look from built-in automatic flash, but it is a far cry from beautiful light. Creating natural-looking images is not nearly as straightforward. Mastering the properties of light and the ability to manipulate, craft, and direct it is a lifelong endeavor. Those diving into Speedlights need some help. Manuals are terse and the terminology is confusing--this is where Mastering Canon EOS Flash Photography comes in. This is the complete book on the subject, guiding you through Canon's Speedlite system, from off-camera portable flash to professional studio lighting. It covers the fundamentals of flash metering technology, discusses key lighting concepts, and documents a wide range of Canon and third-party equipment. Universal flash accessories, studio gear, and radio triggers are all thoroughly covered. The book is lavishly illustrated with diagrams that demonstrate important functions and lighting arrangements, and inspiring photos that show sophisticated flash techniques. Though tailored for users of Canon EOS cameras, owners of other camera systems will find much valuable information as well. So, whether you're just getting started with flash, or you've picked up the bug for off-camera lighting from such popular websites as Strob ...